Sustainable production of housefly (Musca domestica) larvae as a protein-rich feed ingredient by utilizing cattle manure. - Mahmoud Hussein; Viju V Pillai; Joshua M Goddard; Hui G Park; Kumar S Kothapalli; Deborah A Ross; Quirine M Ketterings; J Thomas Brenna; Mark B Milstein; Helene Marquis; Patricia A Johnson; Jan P Nyrop; et al. (PLoS ONE, 2017)
The common housefly, Musca domestica, is a considerable component of nutrient recycling in the environment. Use of housefly larvae to biodegrade manure presents an opportunity to reduce waste disposal while the rapidly assimilated insect biomass can also be used as a protein rich animal feed. In this study, we examine the biodegradation of dairy cattle manure using housefly larvae, and the nutritional value of the resulting larva meal as a feed ingredient. Our results demonstrated that dairy cattle manure presents a balanced substrate for larval growth, and the spent manure showed reductions in concentration of total nitrogen (24.9%) and phosphorus (6.2%) with an overall reduction in mass. Larva yield at an optimum density was approximately 2% of manure weight. Nutritional analysis of M. domestica larva meal showed values comparable to most high protein feed ingredients. Larva meal was 60% protein with a well-balanced amino acid profile, and 20% fat with 57% monounsaturated fatty acids, and 39% saturated fatty acids. Larva meal lacked any significant amount of omega-3 fatty acids. Evaluation of micronutrients in larva meal suggested that it is a good source of calcium and phosphorus (0.5% and 1.1% respectively). The nutritional value of larva meal closely matches that of fishmeal, making it a potentially attractive alternative for use as a protein-rich feed ingredient for livestock and aquaculture operations.